Merkel Cell Carcinoma with Lymphoepithelioma-Like Pattern: A Case Report of an Exceedingly Rare Variant of Merkel Cell Carcinoma with Lymph Node Metastases at Presentation - Soumaya Ben Abdelkrim; Abdelmajid Dhouibi; Adnène Moussa; Rim Hadhri; Leila Njim; Khalifa Mighri; Abdelfatteh Zakhama (Hindawi Limited, 2011)
Merkel cell carcinoma (MCC) or primary neuroendocrine carcinoma of the skin is a rare neoplasm with aggressive behavior. Primary lymphoepithelioma-like (LEL) carcinoma of the skin is a recently described exceptional tumor, with a relatively good prognosis, and is characterized by a neoplastic epithelial component associated with a dense lymphoid stroma. Rarely, MCC shows a marked lymphocytic host response or can even mimic a LEL carcinoma. We report a new case of MCC mimicking an LEL carcinoma in a 72-year-old male; the diagnosis of MCC was made on the basis of the morphology and immunohistochemical findings. We present through this case an exceptional pattern of MCC which can be misleading, and we insist on differential diagnoses.